2003
DOI: 10.1097/01.brs.0000083167.78853.d5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cage Geometry on Sagittal Alignment in Instrumented Posterior Lumbar Interbody Fusion

Abstract: The cage geometry has a significant impact on the alignment of the lumbar spine after instrumented posterior lumbar interbody fusion. With rectangular cages, lumbar lordosis and segmental lordosis of the segments fused decrease; sagittal balance is maintained by compensatory changes of the sacral tilt. Wedge-shaped cages significantly increase segmental lordosis, enhance lumbar lordosis, and therefore should be preferred for restoring sagittal alignment in instrumented posterior lumbar interbody fusion procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(68 citation statements)
references
References 18 publications
3
61
0
4
Order By: Relevance
“…With regard to cage shape, it has been shown that lordotic 'wedged' cages or structural allograft results in greater monosegmental lordosis than non-wedged cages [15,[32][33][34][35]. However, the effect of other cage parameters such as cage height and length has not been previously assessed.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to cage shape, it has been shown that lordotic 'wedged' cages or structural allograft results in greater monosegmental lordosis than non-wedged cages [15,[32][33][34][35]. However, the effect of other cage parameters such as cage height and length has not been previously assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The expandable design of the VariLift ® -L converts the low-profile cylindrical implant to a wedge shaped implant when fully deployed to support preservation of lumbar lordosis. Previous reports have established the importance of restoring and maintaining lordosis with stand-alone cage technologies (12)(13)(14). Additionally, with the PLIF procedure, two bilateral devices are implanted (Figure 1), providing maximal endplate contact which has been shown to be preferable (15).…”
Section: Discussionmentioning
confidence: 99%
“…There are reports that fusion can significantly reduce lumbar lordosis [36], and that this reduction correlates with postoperative back pain [37,38]. However, whether lumbar total disc replacement will influence lumbar lordosis and whether the lumbar lordosis correlates with clinical outcome are controversial [39][40][41].…”
Section: Discussionmentioning
confidence: 99%